Diameters of certain classes of analytical functions. I - Vakarchuk , S. B. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
In the spaces of analytic functions $E_q (Ω), q≥1$,, introduced by V. I. Smirnov, where $Ω$ is a bounded simply connected domain in the plane $\mathbb C$ with sufficiently smooth boundary γ, we obtain order estimates of diameters of the classes $W^rE_p (Ω) (р≥1$, and $r$ is a natural number $≥ 2$) for distinct $p$ and $q$.